2020
DOI: 10.3389/fpsyt.2020.00834
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Nonadherence to Treatment in People Living With HIV: A Systematic Review and Meta-analysis

Abstract: Background: Posttraumatic stress disorder (PTSD) is a commonly reported and serious complication among people living with HIV (PLWH). PTSD may significantly increase unintentional non-adherence to antiretroviral therapy. In this systematic review and metaanalysis, we aimed to pool the observational studies exploring the association between PTSD and medication adherence among PLWH. Methods: Comprehensive searches were conducted in PubMed/Medline, Web of Science, PsycINFO, Google Scholar, and ProQuest to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Therefore, it is worth noting that PTSD has also been shown to be an independent risk factor for medication nonadherence in multiple settings, including HIV, hypertension, and other medical comorbidities, and might have confounded adherence to AUD medications in this study. [14][15][16] Limitations of this study include: (1) a retrospective study design that introduced inherent bias; (2) the relatively small sample size and absence of power calculation; (3) the In conclusion, the results of this study suggest that use of XR naltrexone may improve adherence rates in patients with AUD compared with oral naltrexone or disulfiram, but not in comparison with acamprosate. Patients may have increased adherence if they are seen more often in clinic and have trialed more AUD medications.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, it is worth noting that PTSD has also been shown to be an independent risk factor for medication nonadherence in multiple settings, including HIV, hypertension, and other medical comorbidities, and might have confounded adherence to AUD medications in this study. [14][15][16] Limitations of this study include: (1) a retrospective study design that introduced inherent bias; (2) the relatively small sample size and absence of power calculation; (3) the In conclusion, the results of this study suggest that use of XR naltrexone may improve adherence rates in patients with AUD compared with oral naltrexone or disulfiram, but not in comparison with acamprosate. Patients may have increased adherence if they are seen more often in clinic and have trialed more AUD medications.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it is worth noting that PTSD has also been shown to be an independent risk factor for medication nonadherence in multiple settings, including HIV, hypertension, and other medical comorbidities, and might have confounded adherence to AUD medications in this study. 14 - 16 …”
Section: Discussionmentioning
confidence: 99%
“…As such, adherence has been a focus in HIV research, which has attempted to identify structural and individual-level factors that impede consistent use of antiretrovirals. Within this work, numerous studies have found trauma, including PTSD, to be an important factor driving nonadherence [33].…”
Section: Trauma and Adherencementioning
confidence: 96%
“…Women with HIV are twice as likely to experience trauma compared to women without HIV (Machtinger et al, 2012 ). The diagnosis itself can elicit stress-related symptoms (Katz & Nevid, 2005 ) as well as posttraumatic stress disorder, which accelerates viral progression (Hou et al, 2020 ). Up to 20% of women with HIV also meet criteria for major depressive disorder, which is four times higher than rates among non-HIV women (Morrison et al, 2002 ); they also are more likely to exhibit generalized anxiety disorder (Beer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%